DISTRIBUTED AUCTION BIDDING SYSTEM (DABS) UNTUK KEBERLANGSUNGAN KEMANDIRIAN PETANI MUARO JAMBI: Agriculture;Auction;Brokers;Commodities;Integration. - Limia Budiarti , Rike; Adriana, Windy; Puad, Lailyn (JURNAL AKADEMIKA, 2020)
Agriculture is the engine of the Indonesian economy. Based on the records of the Central Statistics Agency (BPS), in the second quarter of 2017, the agricultural sector continued to make a positive contribution to the Indonesian economy. According to BPS, it is seen that the amount of Indonesia's gross domestic product (GDP) reached Rp 3,366.8 trillion. The data seems to be a scourge when juxtaposed with the fact that the number of farmers in Indonesia is decreasing, this was concluded by BPS in February 2017 which shows that the number of farmers in Indonesia is only 36 million, meaning that only 13.95% of the total population of Indonesia. Given that Indonesia is starting a period of demographic bonus, which means young people of productive age will exceed that of others. The problem becomes more complex when farmers often get unfair prices from middlemen because regulations are not maximally set. This research offers a solution that can make young people see the world of agriculture and plantations is not an embarrassment to become a profession as well as answering farmers' unrest by providing access to fair price stability. The touch of technology makes this solution offered as an adaptive step in facing the challenges of the Industrial Revolution 4.0 era. This research will involve farmers, traders and middlemen as the main actors, they will be given extensive opportunities with the reach of regulations that do not side with anyone. The system offered can also be applied in all regions of Indonesia with unlimited coverage, but this research will involve several farmer groups in several regions of Jambi Province with their respective commodities. This research will produce an application that moves in a new transaction system between farmers as sellers, traders and also middlemen as buyers with fearful regulation.